Novel Associations Within the Tumor Microenvironment: Fibulins Meet ADAMTSs - Fontanil, Tania; Mohamedi, Yamina; Cobo, Teresa; Cal, Santiago; Obaya, Álvaro J. (Frontiers in Oncology, 2019)
The maintenance of tissue homeostasis in any organism is a very complex and delicate process in which numerous factors intervene. Cellular homeostasis not only depends on intrinsic factors but also relies on external factors that compose the microenvironment or cellular niche. Thus, extracellular matrix (ECM) components play a very important role in maintaining cell survival and behavior, and alterations in the ECM composition can lead to different pathologies. Fibulins and ADAMTS metalloproteases play crucial roles in the upkeep and function of the ECM in different tissues. In fact, members of both of these families of secreted multidomain proteins can interact with numerous other ECM components and thus shape or regulate the molecular environment. Individual members of both families have been implicated in tumor-related processes by exhibiting either pro- or antitumor properties. Recent studies have shown both an important relation among members of both families and their participation in several pathologies, including cardiogenesis or cancer. In this review, we summarize the associations among fibulins and ADAMTSs and the effects elicited by those interactions on cellular behavior.